PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA GEOGEBRA TERHADAP KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK KELAS XI SMAN 9 PADANG - Azzuhra, Syifa (Departemen Matematika, 2024)
This study investigates whether the application of DL model with Geogebra on student’s mathematical reasoning ability. This study also describes the development of student’s reasoning ability during the intervention. The population of this study was class XI o SMA Negeri 9 Padang with random sampling. The study design used a Nonequevalent Posttest Only Control Group Design. The study instruments are quizzes and test of mathematical reasoning abilities. The study data were analyzed descriptively and hypothesis testing. Descriptive data analysis shows positive developments in the mathematical reasoning abilities of students in the experimental class. The results of hypothesis testing show that DL model with Geogebra increase mathematical reasoning ability.Keywords – Mathmatical Reasoning Ability, Discovery Learning Model, Direct Learning, Geogebra